Intraspecific phenotype variations in olive barb Systomus sarana (Hamilton, 1822) population from different rivers is possibly linked to locomotive adaptations in caudal fin - Biswal, Jyotsnarni; Singh, Rajeev K.; Mandal, Sangeeta; Chandran, Rejani; Singh, Achal; Sah, Priyanka; Lal, Kuldeep K.; Jena, J. K.; Mohindra, Vindhya (Indian Journal of Fisheries, 2020)
Systomus sarana (Hamilton, 1822) [D1] is an economically important food fish species occurring throughout Indian rivers, which also has ornamental value. This study focused on morphological variations in S. sarana from five river basins across India, viz., Godavari, Mahanadi, Krishna, Middle Ganga and Lower Ganga. A truss network was constructed by interconnecting 12 landmarks to generate 65 morphometric variables extracted from digital images of specimens sampled from the study locations. Transformed truss measurements were subjected to Principal component analysis (PCA), Canonical discriminant function analysis (CDFA), Box plot and Thin plate spline (TPS) analyses. PCA identified eight truss variables with significant loadings, while CDFA designated two truss variables with potential for explaining discrimination between populations. Anterior attachment of dorsal membrane from caudal fin was identified to be the most important variable that presented variations across the river basins studied. Discriminant analysis correctly classified 70.5% of the specimens into their original populations. Thin plate spline for morphometric shape variation analysis indicated highest specimen-shape variations (warping) in Mahanadi basin. TPS-principal strain ratio on principal components (PC-1, PC-2) further revealed significant divergence among the populations in five river basins studied. Results of the study revealed variation in stocks of the species, on the basis of shape morphometry. The four significant parameters, differentiating specimens from different basins, were linked to caudal fin origin at dorsal side and the centre and possibly indicate plasticity in response to locomotive adaptations. Keywords: Plasticity, Populations, Systomus sarana, Truss morphometry